Impact Test Analysis on Steel Metal Materials and Aluminum - Sunarno Sunarno; Zainuddin Zainuddin (International Journal Labs, 2023)
Impact testing is carried out to determine the strength of the material against shock resistance, such as brittleness caused by heat treatment or the brittleness of the casting product and the effect of the shape of the product. This test is carried out on a testing machine designed by having a pendulum with a certain weight that swings from a height to provide shock loads, in this test there are two kinds of testing methods, namely the